2020
DOI: 10.2147/idr.s258355
|View full text |Cite
|
Sign up to set email alerts
|

<p>In-vitro Investigation of Antibiotics Efficacy Against Uropathogenic <em>Escherichia coli</em> Biofilms and Antibiotic Induced Biofilm Formation at Sub-Minimum Inhibitory Concentration of Ciprofloxacin</p>

Abstract: Background: Community-acquired urinary tract infections are associated with significant morbidity, and uropathogenic Escherichia coli (UPEC) alone causes 90% of urinary tract infections. This bacterium retains a diverse armament of virulence factors including fimbria, hemolysins, and siderophores production. In a post invasion scenario, formation of intracellular communities mimic biofilm-like characteristics and are linked to recurrent urinary tract infections. We investigated the effects of different frontli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…This last combination was more effective in reducing the total biomass of the biofilm (~ 50%) than the whole EO (~ 30%). This further demonstrates that biofilm cultures susceptibility to antimicrobials cannot be predicted from the standardized MIC determinations 74 , 75 . Despite not being able to completely eradicate the biofilm biomass, cell culturability was significantly affected, with no colony detected in many of the tested conditions.…”
Section: Discussionmentioning
confidence: 88%
“…This last combination was more effective in reducing the total biomass of the biofilm (~ 50%) than the whole EO (~ 30%). This further demonstrates that biofilm cultures susceptibility to antimicrobials cannot be predicted from the standardized MIC determinations 74 , 75 . Despite not being able to completely eradicate the biofilm biomass, cell culturability was significantly affected, with no colony detected in many of the tested conditions.…”
Section: Discussionmentioning
confidence: 88%
“…The effects of antibiotic on preformed biofilm varied between different in vitro gut conditions. Sub‐MIC of ciprofloxacin has previously been shown to reduce biofilm formation (Dong et al, 2019) while another study showed contrary to the above in that it induced biofilm formation (Rafaque et al, 2020). However, during infection, pathogens are exposed to varied conditions in the gut; therefore, the effect of antibiotics under different in vitro gut conditions need better understanding.…”
Section: Discussionmentioning
confidence: 98%
“…Pereira et al (2007) found only one isolate harbouring qnr among 144 ciprofloxacin-resistant isolates (Pereira et al, 2007). This could be due to other resistance mechanisms such as QRDR mutations or overexpression of efflux pumps in fluoroquinolone-resistant strains (Jazeela et al, 2019;Rezazadeh et al, 2016;Shetty et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hathroubi et al also observed that the sub-MIC penicillin G in Actinobacillus pleuropneumoniae ( A. pleuropneumoniae ) significantly affected biofilms, increased biomass and biofilm thickness, and induced phenotypic changes in biofilm structure [ 31 ]. Similarly, the study by Rafaque et al showed that, in the presence of sub-inhibitory concentrations of ciprofloxacin, the biofilm formation ability of Escherichia coli ( E. coli ) was significantly increased [ 32 ]. Moreover, Mlynek et al found that sub-inhibitory concentrations of Amoxicillin can induce the production of extracellular genes in Staphylococcus aureus ( S. aureus ), thereby stimulating the formation of biofilms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%